Молекулярно-генетичний аналіз поширених мутацій гена АТМ у пацієнтів з підозрою на атаксію-телеангіектазію - Третяк, Б.І.; Макух, Г.В.; Кіцера, Н.І.; Костюченко, Л.В.; Акопян, Г.Р. (Фактори експериментальної еволюції організмів, 2015)
The aim of this study was to conduct of molecular genetic analysis of ATM gene mutations in patients with ataxiatelangiectasia suspection. Methods. DNA was isolated from the peripheral blood cells. DNA was subjected to polymerase chain reaction, RFLP-analysis and electrophoresis in 2 % agarose gel. Results. Molecular genetic testing of ATM gene mutations 7636del9 nt (codon 2546 exon 54), 6095G→A (codon 2003 exon 43), IVS53–2A→C (codon 2544del 159nt exon 54), 5932G→T (codon 1973del88nt exon 42), 3214G→T (codon 1026del207nt exon 24) та 7010 delG→T (codon 2337 exon 50) were performed in 70 probands. In the experimental group was found that 8 probands were heterozygous carriers of ATM gene mutations: one proband — heterozygotes by the mutations IVS53–2A→C and 3214G→T, 2 probands (2.86 %) — heterozygotes by the mutation 5932G→T and 4 probands (5.71 %) — heterozygotes by the mutation 6095G→A. Conclusions. The sequencing of whole ATM gene among patients with unidentified mutations are required to determine the frequency of distribution of other ATM mutations in Ukraine for implementation for practical molecular genetic diagnosis of ataxia-telangiectasia.